2008
DOI: 10.1097/tp.0b013e31817f1686
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering a Complete Vaginal Replacement From a Small Biopsy of Autologous Tissue

Abstract: These data indicate that a tissue engineering approach to clinical vaginal reconstruction in women is now a realistic possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 13 publications
3
50
1
1
Order By: Relevance
“…The cell-seeded matrices were able to regenerate the typical tri-layer vaginal tissue structure with adequate functional parameters long-term ( Figure 3). 9 Similar findings were present when engineering other tissues, such as blood vessels, heart valves, salivary glands, penile tissue, and nerves. [10][11][12][13][14] These studies to date show that scars do not necessarily form for small or superficial wounds or injuries but may be present for deep or larger wounds, often over 3 mm in diameter.…”
Section: Principles Of Wound Healing and Tissue Regenerationsupporting
confidence: 60%
“…The cell-seeded matrices were able to regenerate the typical tri-layer vaginal tissue structure with adequate functional parameters long-term ( Figure 3). 9 Similar findings were present when engineering other tissues, such as blood vessels, heart valves, salivary glands, penile tissue, and nerves. [10][11][12][13][14] These studies to date show that scars do not necessarily form for small or superficial wounds or injuries but may be present for deep or larger wounds, often over 3 mm in diameter.…”
Section: Principles Of Wound Healing and Tissue Regenerationsupporting
confidence: 60%
“…Other tissue sources, including the skin, trachea, and urethral tissue (Raya-Rivera et al, 2011) are also considered (Badylak et al, 2012). Animal studies have indicated that native vaginal tissue is preferable for reconstruction (De Filippo et al, 2008). For clinical practice, unfortunately, native vaginal tissue is limited or unavailable at all in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…De Fillipo et al reported the results of vaginal replacement in a rabbit model using a neovagina engineered from biopsy of autologous vaginal tissue. The presence of functional and histologically normal vaginal tissues represented the opportunity of a very attractive option for surgery reconstruction in patients with MRKH syndrome [24]. Pacini et al reported a case report of modified Abbé-McIndoe technique using autologous in vitro grown vaginal tissue in a patient with vaginal agenesis.…”
Section: Discussionmentioning
confidence: 99%